Biodiversitas Burung Air di Kawasan Mangrove di Sekitar Muara Sungai Lakawali dan Sungai Ussu Kecamatan Malili, Kabupaten Luwu Timur, Sulawesi Selatan: Biodiversity of Water Birds in the Mangrove Area Around the Estuaries of the Lakawali River and Ussu River, Malili District, East Luwu Regency, South Sulawesi - Makkatenni; Jalil; Amirullah; Sitti Wirdhana Ahmad; Muhsin; Nasaruddin (Jurnal Sumberdaya Hayati, 2023)
Water bird diversity in mangrove ecosystem of the Malili District, East Luwu Regency, South Sulawesi, is rarely studied. This reseacrh aims to examine the diversity of bird species in the mangrove ecosystem, Malili District, East Luwu Regency, South Sulawesi. The study was conducted at two stations, namely mangrove forests at the Lakawali River estuary and at the Ussu River estuary. Data collection was carried out using field by field methods, observations were made with binoculars and a Nikon D5200 DSLR camera. Data analysis was performed using the Diversity Index (H’) formula according to Shannon-Winner and evenness index (E) according to Magurren. Species conservation status is determined based on Minister of Environment and Forestry Regulation No. P.106/MENLHK/SETJEN/ KUM.1/12/2018 and IUCN redlist. The results showed that 417 individual birds were found consisting of 5 orders, 7 families and 17 species, there was one protected species, namely great knot (Calidris tenuirostris). The diversity index (H’) in the estuary of Lakawali river is 2.48, and in the estuary of Ussu river is 2.59 which indicates the medium category. The evenness index (E) in the estuary of Lakawali river was 0.92 and in the Ussu River was 0.93 which showed that the distribution of species in both habitats was quite even.